Faktor-Faktor Yang Mempengaruhi Ketidaklengkapan Kunjungan Antenatal Care Pada Ibu Hamil di Puskesmas Beutong Kecamatan Beutong Kabupaten Nagan Raya Provinsi Aceh - Cut Karlina; Srilina Br Pinem; Ernamari Ernamari; Humaida Humaida; Ribur Sinaga (Jurnal Anestesi, 2024)
Pregnancy is the result of the “dating” of sperm and egg. In the process, the sperm's journey to meet the egg (ovum) is really full of struggle. Of the approximately 20-40 million sperm released, only a few succeed in reaching the egg. Pregnancy care is important to ensure that the natural process of pregnancy runs normally and remains so at every antenatal visit after the first antenatal visit until delivery. Pregnancy visits were carried out as many as 6 KN. The aim was to examine the factors that influence the incompleteness of antenatal care visits at the Beutong Community Health Center, Beutong District, Nagan Raya Regency, Aceh Province in 2022. This research uses analytical observational research methods with the research design used by Cross Sectional. The sample in the research was 38 people using accidental sampling. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square Tabulation research results There is a relationship between knowledge and incomplete antenatal care visits at the Beutong Health Center, Beutong District, Nagan Raya Regency, Aceh Province in 2022. This can be seen from the p value = 0.034 > 0.05 with a prevalence ratio of 0.143 (95% CI = 0.058 – 0.354). There is a relationship between family income and antenatal care visits, this can be seen from the p value = 0.049 < 0.05 with a prevalence ratio of 0.214 (95% CI = 0.471 – 0.967). There is no relationship between parity and maternal knowledge about antenatal visits. This can be seen from the p value = 0.094> 0.05 with a prevalence ratio of 1.222 (95% CI = 0.066 – 0.743). There is a relationship between work and incomplete antenatal care visits. This can be seen from the p value = 0.001 < 0.05 with a prevalence ratio 0.77 (95% CI = 0.20 – 0.291). There is a relationship between education and incomplete antenatal visits, this can be seen from the p value = 0.049 < 0.05 with a prevalence ratio of 0.214 (95% CI = 0.471 – 0.967) Conclusion: There is a significant relationship between knowledge and income, employment and education and the incompleteness of antenatal care visits at Beutong Community Health Center, Beutong District, Nagan Raya Regency, Aceh Province in 2022. And there is no relationship between parity and mother's knowledge about antenatal care visits at Beutong Community Health Center, Beutong District, Nagan Regency. Raya Aceh Province in 2022.